Schistosoma haematobium effects on Plasmodium falciparum infection modified by soil-transmitted helminths in school-age children living in rural areas of Gabon. - Jean Claude Dejon-Agobé; Jeannot Fréjus Zinsou; Yabo Josiane Honkpehedji; Ulysse Ateba-Ngoa; Jean-Ronald Edoa; Bayodé Roméo Adegbite; Ghyslain Mombo-Ngoma; Selidji Todagbe Agnandji; Michael Ramharter; Peter Gottfried Kremsner; Bertrand Lell; Martin Peter Grobusch; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Malaria burden remains high in the sub-Saharan region where helminths are prevalent and where children are often infected with both types of parasites. Although the effect of helminths on malaria infection is evident, the impact of these co-infections is not clearly elucidated yet and the scarce findings are conflicting. In this study, we investigated the effect of schistosomiasis, considering soil-transmitted helminths (STH), on prevalence and incidence of Plasmodium falciparum infection. METHODOLOGY:This longitudinal survey was conducted in school-age children living in two rural communities in the vicinity of Lambaréné, Gabon. Thick blood smear light microscopy, urine filtration and the Kato-Katz technique were performed to detect malaria parasites, S. haematobium eggs and, STH eggs, respectively. P. falciparum carriage was assessed at inclusion, and incidence of malaria and time to the first malaria event were recorded in correlation with Schistosoma carriage status. Stratified multivariate analysis using generalized linear model was used to assess the risk of plasmodium infection considering interaction with STH, and survival analysis to assess time to malaria. MAIN FINDINGS:The overall prevalence on subject enrolment was 30%, 23% and 9% for S. haematobium, P. falciparum infections and co-infection with both parasites, respectively. Our results showed that schistosomiasis in children tends to increase the risk of plasmodium infection but a combined effect with Trichuris trichiura or hookworm infection clearly increase the risk (aOR = 3.9 [95%CI: 1.7-9.2]). The incidence of malaria over time was 0.51[95%CI: 0.45-0.57] per person-year and was higher in the Schistosoma-infected group compared to the non-infected group (0.61 vs 0.43, p = 0.02), with a significant delay of time-to first-malaria event only in children aged from 6 to 10-years-old infected with Schistosoma haematobium. CONCLUSIONS:Our results suggest that STH enhance the risk for P. falciparum infection in schistosomiasis-positive children, and when infected, that schistosomiasis enhances susceptibility to developing malaria in young children but not in older children.